No robust evidence of future changes in major stratospheric sudden warmings: a multi-model assessment from CCMI - Ayarzagüena Porras, Blanca; Polvani, Lorenzo M.; Langematz, Ulrike; Akiyoshi, Hideharu; Bekki, Slimane; Butchart, Neal; Dameris, Martin; Deushi, Makoto; Hardiman, Steven C.; Jöckel, Patrick; Klekociuk, Andrew; Marchand, Marion; et al. (Atmospheric Chemistry and Physics, 2018)
Major mid-winter stratospheric sudden warmings (SSWs) are the largest instance of wintertime variability in the Arctic stratosphere. Because SSWs are able to cause significant surface weather anomalies on intra-seasonal timescales, several previous studies have focused on their potential future change, as might be induced by anthropogenic forcings. However, a wide range of results have been reported, from a future increase in the frequency of SSWs to an actual decrease. Several factors might explain these contradictory results, notably the use of different metrics for the identification of SSWs and the impact of large climatological biases in single-model studies. To bring some clarity, we here revisit the question of future SSW changes, using an identical set of metrics applied consistently across 12 different models participating in the Chemistry–Climate Model Initiative. Our analysis reveals that no statistically significant change in the frequency of SSWs will occur over the 21st century, irrespective of the metric used for the identification of the event. Changes in other SSW characteristics – such as their duration, deceleration of the polar night jet, and the tropospheric forcing – are also assessed: again, we find no evidence of future changes over the 21st century. European Research council Deutsche Forschungsgemeinschaft Depto. de Física de la Tierra y Astrofísica Fac. de Ciencias Físicas TRUE pub